Phenotypic and genotypic characteristics of cryopyrin-associated periodic syndrome: a series of 136 patients from the Eurofever Registry. Issue 11 (18th July 2014) - Levy, R; Gérard, L; Kuemmerle-Deschner, J; Lachmann, H J; Koné-Paut, I; Cantarini, L; Woo, P; Naselli, A; Bader-Meunier, B; Insalaco, A; Al-Mayouf, S M; Ozen, S; et al.
Abstract : Objective: To evaluate genetic, demographic and clinical features in patients with cryopyrin-associated periodic syndrome (CAPS) from the Eurofever Registry, with a focus on genotype-phenotype correlations and predictive disease severity markers. Methods: A web-based registry retrospectively collected data on patients with CAPS. Experts in the disease independently validated all cases. Patients carrying NLRP3 variants and germline-mutation-negative patients were included. Results: 136 patients were analysed. The median age at disease onset was 9 months, and the median duration of follow-up was 15 years. Skin rash, musculoskeletal involvement and fever were the most prevalent features. Neurological involvement (including severe complications) was noted in 40% and 12% of the patients, respectively, with ophthalmological involvement in 71%, and neurosensory hearing loss in 42%. 133 patients carried a heterozygous, germline mutation, and 3 patients were mutation-negative (despite complete NLRP3 gene screening). Thirty-one different NLRP3 mutations were recorded; 7 accounted for 78% of the patients, whereas 24 rare variants were found in 27 cases. The latter were significantly associated with early disease onset, neurological complications (including severe complications) and severe musculoskeletal involvement. The T348M variant was associated with early disease onset, chronic course and hearing loss. Neurological involvement was less strongly associated with V198M, E311 K and A439 V alleles. Early onset was predictive of severe neurological complications and hearing loss. Conclusions: Patients carrying rare NLRP3 variants are at risk of severe CAPS; onset before the age of 6 months is associated with more severe neurological involvement and hearing loss. These findings may have an impact on treatment decisions.